El efecto del beneficiado del café sobre los insectos acuáticos en tres ríos del Valle Central (Alajuela) de Costa Rica - Fernández, Leonel; Springer, Monika (Revista de Biología Tropical, 2008)
The effect of coffee processing on aquatic insects in three rivers from the Central Valley (Alajuela) of Costa Rica. In Costa Rica one of the greatest sources of organic pollution in the rivers has been the residual material generated from the processing of coffee beans. In this study, the usefulness of aquatic insects as bioindicators is examined in order to measure the effect of spills of coffee processing plants into two rivers of the Central Valley. The study was conducted at three different coffee processing plants at the three most important moments of the harvest, at the beginning, the peak and at the end. On each of the three dates, biological samples were taken 50m up- and 50m down-stream from the point where the coffee processing plants discharge their liquid wastes. The following physical and chemical factors were also measured: DBO, DQO, pH, temperature, fats and oils, sedimentable solids, dissolved oxygen and the discharge of the river. Systematic samples of aquatic insects were taken in order to obtain relative abundance, taxa richness, diversity (Shannon-Wiener), similarity (Bray-Curtis) and biological index B.M.W.P.’ (Biological Monitoring Working Party) adapted for Costa Rica. Physical-chemical results showed a decrease in the amount of dissolved oxygen and in the discharge of the rivers. In addition, in some cases very high values of DBO and DQO were reached as the season advanced; nevertheless, the majority of the measurements taken were within the limits established by the laws of Costa Rica. Populations of insects increased down stream as the season advanced, due mainly to an increase in the density of Chironomus larvae (Diptera) which became the dominant group. At the same time other pollution sensitive taxa diminished or disappeared. This was reflected by decreasing taxonomic richness and a low diversity index. Similarity between samples taken up and down stream was less than half (0,41), and comparing the three main harvest moments, the highest point was very similar to the end of the harvest (0,81) and both were very different from the beginning of the harvest (0,26). According to the modified biological index BMWP’, water quality diminished to category “strongly contaminated” at the highest point of the harvest. The results indicate that there is an important effect on the populations of aquatic insects caused by the period of harvest, which is not necessarily detected by the standard analysis required by law. Therefore we recommend that the fauna of aquatic macroinvertebrates should be included as a mandatory procedure in water quality testing, the capacity of the treatment plants should be evaluated, and the standard limits established by present laws in Costa Rica, should be critically analyzed. Rev. Biol. Trop. 56 (Suppl. 4): 237-256. Epub 2009 June 30.